Influence of Loudspeaker Configurations and Orientations on Sound Localization - YAO, Shu-Nung (Archives of Acoustics, 2022)
As the virtual reality (VR) market is growing at a fast pace, numerous users and producers are emerging with the hope to navigate VR towards mainstream adoption. Although most solutions focus on providing high- resolution and high-quality videos, the acoustics in VR is as important as visual cues for maintaining consistency with the natural world. We therefore investigate one of the most important audio solutions for VR applications: ambisonics. Several VR producers such as Google, HTC, and Facebook support the ambisonic audio format. Binaural ambisonics builds a virtual loudspeaker array over a VR headset, providing immersive sound. The configuration of the virtual loudspeaker influences the listening perception, as has been widely discussed in the literature. However, few studies have investigated the influence of the orientation of the virtual loudspeaker array. That is, the same loudspeaker arrays with different orientations can produce different spatial effects. This paper introduces a VR audio technique with optimal design and proposes a dual-mode audio solution. Both an objective measurement and a subjective listening test show that the proposed solution effectively enhances spatial audio quality.